Industrial Processes Online Teaching: A Good Practice for Undergraduate Engineering Students in Times of COVID-19 - Ricaurte Fernández, Marvin José (2022)
The COVID-19 pandemic required higher education institutions to change the modality of face-to-face to online learning overnight. Adaptations were needed, particularly in industrial process training in Chemical Engineering and related careers. Students could not access companies and industries for internships or industrial visits, intended to allow undergraduate students to observe the process engineers’ work in professional spaces. This paper describes a pedagogical strategy to overcome this limitation. Here, we report an approach applied in an Industrial Processes course, with students from the 8th to 10th semesters and alumni, from the undergraduate Petrochemical Engineering program at Yachay Tech University (Ecuador). In this course, the students developed group projects involving an industrial process analysis focused on economic sectors of interest in the country. The projects also included a revision of official figures and statistics on production data, consumption, and perspectives of the different markets. The execution of these projects promoted students’ active participation through technical discussions by exchanging ideas. A high level of attendance at synchronic classes reflected a high motivation. Through feedback and interviews, the students’ comments confirmed the relevance and value of the strategy applied in the course.